How Important is Bioturbation for Sediment‐to‐Water Flux of Polycyclic Aromatic Hydrocarbons in the Baltic Sea?. (25th July 2019) - Mustajärvi, Lukas; Nybom, Inna; Eriksson‐Wiklund, Ann‐Kristin; Eek, Espen; Cornelissen, Gerard; Sobek, Anna
Abstract: In the present study a recently developed benthic flow‐through chamber was used to assess the sediment‐to‐water flux of polycyclic aromatic hydrocarbons (PAHs) at 4 sites on the Swedish Baltic Sea coast. The flow‐through chamber allows for assessment of the potential effect of bioturbation on the sediment‐to‐water flux of hydrophobic organic contaminants. The sediments at the 4 investigated sites have both varying contamination degree and densities of bioturbating organisms. The flux of individual PAHs measured with the flow‐through chamber ranged between 21 and 510, 11 and 370, 3 and 9700, and 62 and 2300 ng m –2 d –1 for the 4 sites. To assess the potential effect of bioturbation on the sediment‐to‐water flux, 3 flow‐through and closed chambers were deployed in parallel at each site. The activity of benthic organisms is attenuated or halted because of depletion of oxygen in closed benthic chambers. Therefore, the discrepancy in flux measured with the 2 different chamber designs was used as an indication of a possible effect of bioturbation. A potential effect of bioturbation on the sediment‐to‐water flux by a factor of 3 to 55 was observed at sites with a high density of bioturbating organisms (e.g., Marenzelleria spp., Monoporeia affinis, and Macoma balthica of approximately 860–1200 individuals m –2 ) but not at the site with much lower organism density (<200 individuals m –2 ). One site had a high organism density and a low potential effect of bioturbation, which we hypothesize to be caused by the dominance of oligochaetes/polychaetes at this site because worms ( Marenzelleria spp.) reach deeper into the sediment than native crustaceans and mollusks. Environ Toxicol Chem 2019;38:1803–1810. © 2019 SETAC Abstract : Sediment‐to‐water flux of legacy persistent organic pollutants determined by 2 types of benthic chambers: one flow‐through chamber allowing for bioturbation, and 1 closed chamber with no bioturbation. The photo to the right shows the chambers before they are placed on the sediment.